Sodna praksa v zvezi z obstojem delovnega razmerja in fleksibilnimi oblikami zaposlitve - Robnik, Ivan (Delavci in delodajalci, 2012)
The paper presents the case law concerning the existence of an employment relationship on the grounds of the work actually carried out and in relation to some flexible forms of employment. In the first place, the courts had to define the conditions for legal protection regarding the existence of such relationships. According to the definition of the labour relationship and the legal regulations on employment contract, the Supreme Court of the Republic of Slovenia adopted a rather broad interpretation regarding the existence of labour relationship on the grounds of the work actually carried out which includes elements characteristic for the labour relationship.
Keywords: delovna razmerja; delovno pravo; kršenje; pogodba o zaposlitvi; procesno pravo; sodna praksa